Development of volunteer service system using mobile application with notification features / Fakhrul Iqram Rafien - Fakhrul Iqram Rafien (2017)
Volunteer Service System (VSS) is a mobile application that have been developed to help volunteers in Kelantan in finding volunteer service and also as a platform for volunteer organization to handle and manage their volunteer service. Nowadays volunteer service is an important value for the communities because it help communities to make their relationship to be stronger. VSS be developed to cater a problem that face by volunteers and organization. Based on survey and interview with stakeholder which is The 3rd Force, there are five problem that faced by organization and volunteers. The problem faced by organization are difficult to find volunteers cause by not many platform that can be used, they do not know how many volunteers are willing to join their event and time consuming to find volunteers. While the problem faced by volunteers are insufficient information about volunteer service that they can read and don’t know where to find volunteer service because of not many platform can be used. As a guidelines for development of the system, it will follow a methodology which is Mobile Application Development Lifecycle (MADLC). MADLC consist six phases which is requirement identification, design, development, prototyping, testing and maintenance. However only three phases are be choose which is identification, design and development. Every phases have its own activities and the activities be followed to achieve the project objectives. As a result after every activities in every phases have been done, an application name as “Volunteer Service “was developed together with Software Requirement Specification (SRS) and Software Design Document (SDD). Last but not least, for the future work, this system will be improved more based on recommendation that have been discussed.